The functional analysis of XhLEA3-2 - a LEA_4 from the resurrection plant, Xerophyta humilis - Dennis, Timothy James (Department of Molecular and Cell Biology, 2018)
Climate change is a pressing reality in the current era. Changing environmental conditions and limited water availability are associated with the loss of arable land in areas where farming has traditionally thrived. Thus, linked to climate change, is the risk of a global food shortage. Resurrection plants are phenomenal in that they are able to survive extended periods of drought in a state of anhydrobiosis and then resume full metabolism upon rehydration. These plants serve as models to scientists and genetic engineers who hope to replicate, to a degree, the 'resurrection phenomenon' in drought sensitive crop species. The ability of resurrection plants to survive drought needs to be studied on a molecular level if it is to be implemented in transgenic crops. Currently, the molecular mechanisms of desiccation tolerance are only somewhat understood, and considerable investigation is still required. Xerophyta humilis is a monocotyledonous resurrection plant in which one of the responses to extreme water loss is the upregulation of several Late Embryogenesis Abundant (LEA) genes. The protein products of these genes, called LEA proteins, are known to be correlated with abiotic stress tolerance in plants, invertebrates and microorganisms. However, the precise molecular mode(s) of action of LEA proteins are still poorly understood. In this study, a group LEA_4, LEA protein, which we have termed XhLEA3-2, shown to be transcriptionally upregulated during desiccation of the resurrection plant X. humilis, has been characterized. A bioinformatic, predictive analysis was performed to detect any LEA-like characteristics of XhLEA3-2. Recombinant XhLEA3-2 was produced in Escherichia coli, purified, and used to generate XhLEA3-2 specific antibodies for expression analyses. The ability of XhLEA3-2 to function as a molecular chaperone was assessed using a lactate dehydrogenase (LDH) enzyme stability assay. Transgenic expression of XhLEA3-2 in E. coli and tobacco was also investigated. In summary, this thesis demonstrates that XhLEA3-2: has typical LEA protein properties according to bioinformatic analyses, has two close homologs in X. viscosa, is present in dry X. humilis leaf tissue, has homologs present in dry X. viscosa leaf tissue, has some molecular chaperone activity, can protect E. coli from desiccation but not from osmotic stress, and can be transiently expressed in tobacco.